1967
DOI: 10.1246/bcsj.40.2018
|View full text |Cite
|
Sign up to set email alerts
|

The Stereoselection Rule for Electrocyclic Interactions

Abstract: A general stereoselection rule governing the electrocyclic interactions has been proposed with a molecular orbital rationale. The reactions discussed from a unified point of view cover the ring-closure of polyenes, the Diels-Alder additions, 1,4-dipolar additions, the Cope and the Claisen rearrangements, the hydrogen and the proton migrations, 1,3-dipolar additions, the ring-opening of cyclic olefins, the deamination of cyclic unsaturated imines, 1,2-noncycloadditions, 1,2-eliminations, the nucleophilic displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In fact, whereas electrostatic potential minima indicate an 8 kcaVmol preference for exo over endo attack of the double bond, vertical proton affinities favor endo over exo protonation by about 2 kcaVmo1. The inference that without nuclear relaxation in the non-planar equilibrium structure of vinyl amine proton addition to the nitrogen and the P-carbon atom should occur preferentially from opposite sides of the molecule is of particular interest in view of continuing discussions concerning similar alternations in the stereochemical mode of substitution and elimination reactions involving allylic systems [4] [26] [27].…”
Section: Electrostatic Potentials Of Vinyl Amine With Respect To a Pomentioning
confidence: 99%
“…In fact, whereas electrostatic potential minima indicate an 8 kcaVmol preference for exo over endo attack of the double bond, vertical proton affinities favor endo over exo protonation by about 2 kcaVmo1. The inference that without nuclear relaxation in the non-planar equilibrium structure of vinyl amine proton addition to the nitrogen and the P-carbon atom should occur preferentially from opposite sides of the molecule is of particular interest in view of continuing discussions concerning similar alternations in the stereochemical mode of substitution and elimination reactions involving allylic systems [4] [26] [27].…”
Section: Electrostatic Potentials Of Vinyl Amine With Respect To a Pomentioning
confidence: 99%
“…Carrion and Dewar suggest that the predominance in solution of the S N 2 mechanism over the S N 2‘ one is primarily due to energy-demanding ion desolvation in the S N 2‘ transition structure, which mostly contributes to the building up of the relevant activation barrier, whereas the more favored S N 2 barrier is essentially determined by electronic factors. In light of these modern concepts, these and other authors conclude that there is no real reason concerted S N 2‘ reaction should not be feasible in the gas phase. This indication has been followed in a recent gas-phase study of acid-induced nucleophilic substitution on some allylic alcohols that showed that the concerted S N 2‘ reaction actually competes with the classical S N 2 pathway in the absence of solvation and ion-pairing factors. The same modern concepts consider restrictive any theoretical rationale of the S N 2‘ stereochemistry simply based on stereoelectronic factors, since an important role may be played by Coulombic interactions between NuH and LG and among these and the reaction medium.…”
Section: Introductionmentioning
confidence: 99%
“…Let us first explore the relative aromatic (resonance) 22 character of pyrrole and its derivatives through bond order uniformity 23 and the frontier molecular orbital (FMO) 24 energy gap 25 computed with the AM1 semiempirical method (Table 1). According to the bond order uniformity approach, 23 the ring systems that have the most uniform bond order distributions are the most stable ones.…”
Section: Resultsmentioning
confidence: 99%